THE RELEVANCE OF THE HADITH ON THE ANGELS' CURSE UPON A WIFE WHO REFUSES HER HUSBAND'S INVITATION IN THE CONTEXT OF MARITAL RAPE - Qurota Ayunin Nissa; Ahmad Fudhaili (SOSIOEDUKASI, 2026)
The hadith concerning the angels' curse upon a wife who refuses her husband's invitation has often been interpreted literally as imposing an absolute obligation on wives to fulfill their husbands' sexual demands. Such an interpretation may lead to the justification of marital rape, namely forced sexual intercourse within marriage without the spouse's consent. This study aims to examine the authenticity of the hadith, analyze its meaning, and explain its relevance to the phenomenon of marital rape. This research employs a library research method using a thematic (maudhu'i) hadith approach. The analysis includes takhrīj al-ḥadīth, sanad and matn criticism, interpretation based on classical hadith commentaries and scholarly opinions, and contextual analysis in relation to marital rape. The findings reveal that the hadith is ṣaḥīḥ in terms of sanad, as it fulfills the criteria of an authentic hadith through a continuous chain of transmission, trustworthy narrators, and the absence of shudhūdh and 'illah. Although the matn does not contradict the Qur'an or other relevant hadiths, its interpretation requires a contextual approach to avoid misogynistic implications. The angels' curse applies only to a wife's refusal without legitimate excuse ('udhr shar'i), rather than to every form of refusal. Therefore, the hadith cannot be used to justify marital rape but should instead be understood as an ethical guideline for fostering marital relations based on mu'āsharah bi al-ma'rūf, balanced rights and responsibilities, and the objectives of Islamic law in establishing a just, harmonious, and compassionate family. This study contributes a contextual interpretation of the hadith that prevents its misuse as a justification for sexual violence within marriage.